Development of Content MOOCs: Designing a Creativity Assessment for Elementary School Students in a Learning Management System (LMS) with a Self-Paced Instruction Model - Dwikoranto, Dwikoranto; Lintangesukmanjaya, R T; Surasmi, W A; Suparti, Suparti; Putra, D A; Khansa, I H; Dewi, P A R (STKIP PGRI Tulungagung, 2025)
Becoming a world-class open and distance learning university involves developing academic products by improving the quality of academic services and service reach for the entire community. Therefore, developing MOOC content in UT's Learning Management System (LMS) using the Self-Paced Instruction model is crucial. The lack of topics in UT's MOOCs needs to be addressed wisely. The issues to be addressed are the validity of the MOOC content on the topic of Designing an Assessment of Creativity for Elementary School Students linked to the UT LMS, and the competencies/learning outcomes and responses of students using the developed online course, This development research design uses the four-D model (4-D model), adapted from Thiagarajan et al., with the stages Define, Design, Develop, and Disseminate. The research was conducted at the UT Surabaya UPBJJ (Education and Training Center) and Unesa (Unesa) as a collaborative research and development partner. Data were obtained from expert validation of MOOC content, learning outcomes, and responses from online course participants during limited trials in the Bojonegoro and Lamongan Learning Groups (Pokjar). The validation data from three education experts were described and the mean was determined. The online course participant test scores were reviewed and compared against the graduation criteria established by UT. The questionnaire response data was analyzed using percentages and described qualitatively. The development of the MOOC content for elementary school students' Creativity Assessment was found to be valid and reliable. Student learning outcomes improved. Students provided very positive responses, and the MOOCs can be accessed by all users of the UT LMS